1984
DOI: 10.1021/bi00315a016
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer membranes containing the ganglioside GM1: models for electrostatic potentials adjacent to biological membranes

Abstract: Although the Gouy-Chapman-Stern theory of the aqueous diffuse double layer describes well the electrostatic potential adjacent to negatively charged phospholipid bilayer membranes, it does not describe adequately the zeta potential of biological membranes: the zeta potential of an erythrocyte is about half the value predicted from the theory by using the known density of negatively charged sialic acid residues. To investigate the factors responsible for this low electrophoretic mobility, we formed membranes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 35 publications
4
51
1
Order By: Relevance
“…Moreover, sonicated liposomes present a higher polydispersity and are intrinsically less stable because their structure undergoes more changes as a function of time than the extruded liposomes. In MLV liposomes formed by 20% of PS, McDaniel et al (15) reported a zeta potential of Ϫ75 mV, whereas for the same composition we found a value of Ϫ73.9 Ϯ 5.1 mV.…”
Section: Discussioncontrasting
confidence: 41%
“…Moreover, sonicated liposomes present a higher polydispersity and are intrinsically less stable because their structure undergoes more changes as a function of time than the extruded liposomes. In MLV liposomes formed by 20% of PS, McDaniel et al (15) reported a zeta potential of Ϫ75 mV, whereas for the same composition we found a value of Ϫ73.9 Ϯ 5.1 mV.…”
Section: Discussioncontrasting
confidence: 41%
“…Liposomes consisting of 20% PG or 20% PS also have a similar zeta potential value. Vesicles formed from 5:1 PC:PG or 5:1 PC:PS mixtures have been found to have similar zeta potentials (40,42). This correlation is slightly reduced at low percentages (5%) of anionic lipid, between liposomes composed of PG and PS, with a R 2 value of 0.977 for 17 drugs.…”
Section: Effect Of Liposome Compositionmentioning
confidence: 95%
“…5. Many detailed discussions on the effect of anionic lipid content on the zeta potential have been published (40)(41)(42). Zeta potentials have been found to have an exponential dependence on the PS content in liposomes (43).…”
Section: Effect Of Liposome Compositionmentioning
confidence: 99%
“…The local electrical potential at the surface of a phospholipid monolayer containing acidic lipids was calculated according to the Guy-Chapman-Stern (G-C-S) theory (Aveyard and Haydon, 1973), as discussed, for example in Eisenberg et al (1979) and McDaniel et al (1984). Both screening and specific binding of counterions (protons and Na+ ions in our case) were taken into account.…”
Section: Appendix C: Estimation Of the Surface Potential Of The Lipidmentioning
confidence: 99%